Health & human development in the new global economy : the contributions and perspectives of civil society in the Americas - Bambas, Alexandra...[et al] (PAHO WashingtonUS, 2000)
Examines the impact of the economic globalization process and technological change on health trends in the region of the Americas. Focuses on how civil groups can influence the formulation of healthy public policies and monitor equity, in terms of both the health situation and the distribution of health care resources.